Colonialism and religion: colonial knowledge productions on Sri Pada as ‘Adam’s Peak’ - De Silva, Premakumara (My University, 2014)
Abstract: This paper is directed to discuss the ‘effective’aspect of colonial knowledge in the discursive constructions of one of the popular pilgrimage sites, Sri Pada in Sri Lanka. What the author explores here is how different authoritative discourses emerge about Sri Pada from the different colonial powers: Portuguese (1505-1687), Dutch (1687-1896) and British (1896- 1948). Authoritative discourse on the ‘colonised’ was largely produced through the agents of the colonial governments, military personnel, Christian missionaries, philologists and administrators. In this regard, Sri Pada, or Adam’s Peak as it was called by colonial powers, was not exceptional. These forms of knowledge production change with changes in the practices of colonialism. In this respect, this paper investigates what gets identified and counted by colonial authorised knowledge as ‘Adam’s Peak’. Such an investigation is not new to anthropology and the human sciences in general. A large body of knowledge has been produced in the last two decades to unpack ‘a particular construction of colonial knowledge’ (Pels, 1997). However, a limitation in such an analysis can be seen, because most of the ‘decolonising projects’ in South Asia (India and Sri Lanka) have located their fields of work and expertise in the 19th and 20th centuries to unpack ‘British colonial knowledge production’ and they have paid scanty attention to ‘pre-British knowledge production’; for example, as far as India and Sri Lanka are concerned, the Portuguese and the Dutch ‘colonial knowledge productions’. A reasonably comprehensive understanding of culture, religion and history of the various sub-continental regions in the early 18th century and before is a prerequisite for the understanding of the transformations which the British instituted.
Keywords: Religion, colonialism, knowledge production